2005
DOI: 10.1021/jp050374k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Electronic Properties of Metallic Atom in Bondage to a Nanospace

Abstract: The possibility of modulating the electronic configurations of the innermost atoms inside a nanospace, nano sheath with chemical modification was investigated using synchrotron X-ray photoelectron spectroscopy. Systems of definite nanostructures were chosen for this study. Systematic variations in energy, intensity, and width of pi and sigma O 1s core level spectra, in absorption characteristics of C 1s-->pi transition, in photoabsorption of pre-edge and resonance regions of the Gd 4d-->4f transition, were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 40 publications
0
68
0
Order By: Relevance
“…Gd@C 82 (OH) 22 and C 60 (OH) 22 nanoparticles synthesized as previously described have been well characterized 19 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gd@C 82 (OH) 22 and C 60 (OH) 22 nanoparticles synthesized as previously described have been well characterized 19 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[Gd@C 82 (OH) 22 ] n nanoparticles were prepared as described previously (Xing et al, 2004;Tang et al, 2005) The nanoparticle characterizations have been described by our group (Chen et al, 2005). In brief, the average size of [Gd@C 82 (OH) 22 ] n particles in saline solution was 22 nm in diameter, which was measured by high-resolution atomic force microscopy and synchrotron radiation small-angle scattering.…”
Section: Methodsmentioning
confidence: 99%
“…It possesses a virus-like nanostructure, consisting of a magnetic metal core of a gadolinium (Gd) atom and a closed outer nanosheath of carbon atoms, which are further modified by about 22 outermost hydroxyl groups ( Figure 1) [9]. Several studies have found that the composition and numbers of the outer groups are largely responsible for the bioactive properties of fullerenol molecules [5,7,[14][15][16][17][18]. The Gd@C 82 (OH) 22 molecule is smaller than 2 nm, but Gd@C 82 (OH) 22 tends to aggregate in aqueous solutions and forms dispersed Gd@C 82 (OH) 22 nanoparticles with an average diameter of about 100 nm, which is a ubiquitous property identified in metallofullerenol studies [7].…”
Section: Characterizationmentioning
confidence: 99%